Shoulder Pain in Covid-19 Survivors Following Mechanical Ventilation - Del Valle-Valdes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
COVID-19 has caused a certain proportion of patients to be hospitalized in intensive care units (ICU) and may cause musculoskeletal and neurological deficits following intubation and mechanical ventilation. The aim of this study was to quantify and describe the presence of shoulder pain in patients released from hospitals after suffering COVID-19. Patients with positive Apley tests were sent to a physiatrist for a clinical evaluation, ultrasound and electromyography (EMG). This evaluation was completed with a pain scale, joint range and shoulder muscle strength evaluations. Of the one-hundred-sixteen patients, seventy eight entered the respiratory rehabilitation program. Twenty patients were sent to the multidisciplinary shoulder team for positive Apley scratch tests. Of these twenty patients, one had only an EMG, ten had only ultrasounds, seven had an EMG and ultrasound and two did not need complementary tests. The twenty patients were sent to the physical therapist, with all presenting pain and diminished joint range and muscle strength in the affected shoulder. In this context, shoulder pain could be associated with the prone position in the ICU. We suggest time control and position change for patients on mechanical ventilation in a prone position with COVID-19. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: anatomy; pain; shoulder; COVID-19; peripheral nervous systems